2020
DOI: 10.1111/and.13580
|View full text |Cite
|
Sign up to set email alerts
|

Can subfoveal choroidal thickness replace subjective tests in patients using tadalafil to treat erectile dysfunction?

Abstract: We aimed to determine the effect on choroidal thickness of daily 5 mg tadalafil use in patients with erectile dysfunction (ED) and to evaluate agreement between short form of International Index of Erectile Function (IIEF 1–5, 15) scores and choroidal thickness during follow‐up. Enhanced depth imaging spectral domain–optical coherence tomography (EDI‐OCT) was used to measure full choroidal thickness in the subfoveal area, choroidal thickness (CT) and small‐choroidal‐vessel‐layer (SCVL) thickness. Thirty of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The choroidal thickening was attributed to the expansion of the stroma rather than vascular dilatation [ 23 ]. Recently Aslan et al observed an increase in small-choroidal-vessel-layer (choriocapillaris plus Sattler’s layer) and total choroidal thickness after 3 months of daily oral 5 mg tadalafil in patients with or without erectile dysfunction [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The choroidal thickening was attributed to the expansion of the stroma rather than vascular dilatation [ 23 ]. Recently Aslan et al observed an increase in small-choroidal-vessel-layer (choriocapillaris plus Sattler’s layer) and total choroidal thickness after 3 months of daily oral 5 mg tadalafil in patients with or without erectile dysfunction [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study has shown that this increase in CT may persist with chronic usage of the taladafil. 49 Phosphodiesterase-5 inhibitors are categorized as a possible risk factor for central serous chorioretinopathy, as current data are inconclusive as to whether phosphodiesterase-5 inhibitors cause central serous chorioretinopathy. 91 3.6 | Psychiatric and addictive substances…”
Section: Phosphodiesterase-5 Inhibitorsmentioning
confidence: 99%